Theoretical foundations of regional monetary integration and the practice of forming its prerequisites in the EAEU - Tovma, Natali; Zhaxygulova, G; Kuat, K (Farabi Journal of Social Sciences, 2019)
The article discusses the historical, political and fundamental economic prerequisites for the transition to monetary integration within the framework of the EAEU at the present stage of its development. The purpose of the study is to identify the readiness degree of the EAEU member countries transition to integration in the monetary sphere in modern conditions. The study makes it possible to substantiate the idea that a currency union in the framework of regional economic integration should be viewed as a natural result of significant volumes of goods, services and investments movement between member countries. The necessity and possibility of creating a currency union are determined and evaluated from the standpoint of the trade intensity and investment flows between the member countries of the Eurasian Economic Union. The methodology of the study is based on the key ideas of the “optimum currency areas” theory. The statistical data on foreign investments in the EAEU countries, on the share of gross volumes of mutual trade in the total volume of foreign trade in the EAEU as a whole and in the EAEU member states, are given. Analysis of mutual trade and investment indicators showed an insufficient level of economic convergence in the EAEU, assessed from the standpoint of the mutual trade intensity and mutual foreign direct investment intensity. At the moment, the volumes and dynamics of trade and investment flow between the EAEU member states do not cause an objective need for a transition to monetary cooperation at the level of a currency union. This research allows us to consider the problem of transition to monetary integration between the countries participating in the EAEU from the importance standpoint of economic prerequisites. The practical significance of the work lies in the substantiation of the objective prerequisites for the formation and creation of a monetary union in the course of regional integration processes development. Key words: Currency union, optimal currency area, mutual trade intensity, mutual investment intensity, customs union.